2019
DOI: 10.9734/jeai/2019/v32i230097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage Duration on The Toxicity of Moringa oleifera (Moringaceae) Oil to Tetranychus urticae (Acari: Tetranychidae)

Abstract: The objective of this study was to evaluate the storage time of Moringa oleifera oil on the acaricidal activity on Tetranychus urticae. Was used amber bottle for storage of oil which remained in a room at 25°C. The storage times considered in the experiment were 0, 30, 60, 90 and 120 days after extraction. At each time a suspension at the concentration of 3% (v/v) was applied on the mite. A completely randomized design with 5 treatments (storage times) was used, containing 8 replicates, composed of 12 females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Mostafa et al [23] studying the allelopathic effect of Alhagi maurorum extract as a phytocaricide against the mite Panonychus citri (Acari: Tetranychidae), found an increase in the mortality rate of individuals due to the presence of tannin compounds. Flavonoid compounds, although observed in smaller amounts in this study, act on insects and mites by altering enzymatic and hormonal activity, blocking biochemical pathways, and consequently reducing the assimilation of essential substances and nutrient storage [20]. Studies carried out by Stec et al [24], using ethanolic solutions of the flavonoids apigenin, daidzein, genistein, and kaempferol against the soybean aphid Aphis glycines Matsumura (Hemiptera: Aphididae), found changes in the behavior of the studied aphids.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Mostafa et al [23] studying the allelopathic effect of Alhagi maurorum extract as a phytocaricide against the mite Panonychus citri (Acari: Tetranychidae), found an increase in the mortality rate of individuals due to the presence of tannin compounds. Flavonoid compounds, although observed in smaller amounts in this study, act on insects and mites by altering enzymatic and hormonal activity, blocking biochemical pathways, and consequently reducing the assimilation of essential substances and nutrient storage [20]. Studies carried out by Stec et al [24], using ethanolic solutions of the flavonoids apigenin, daidzein, genistein, and kaempferol against the soybean aphid Aphis glycines Matsumura (Hemiptera: Aphididae), found changes in the behavior of the studied aphids.…”
Section: Resultsmentioning
confidence: 46%
“…While for total flavonoids, the values were in insignificant amounts (Table 2). Most of the plant's defense mechanisms are concentrated in the seeds, given their great importance as a vehicle for the propagation and survival of the species, which is why there is probably the highest concentration of total phenolics in the soursop seed extract [20]. The higher or lower concentration of these compounds is generally determined by exogenous factors such as light, precipitation, place of cultivation, spacing, and sun, as well as by endogenous factors such as plant age and genetic variability in populations [11].…”
Section: Resultsmentioning
confidence: 99%
“…(Coleoptera: Bruchidae) [19] , verifying high mortality rates and reduced egg production when applied to adults in contact and fumigation tests using moringa root oil. Holtz et al [20] found increased efficiency in the mortality of T. urticae using Moringa seed oil at different storage times. Phytochemical analysis of moringa seed extract found large amounts of phenolic compounds, these being flavonoids and tannins [21] in addition to alkaloids, saponins, glycosides, among others [22] .…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that should be considered is the amount of toxins presents in castor bean cake and if there is seasonal variability due to the harvest and storage time, and the effect on the toxicity of these substances. A study carried out with Moringa oleifera (Moringaceae) demonstrated increased toxicity over time of storage on the mite Tetranychus urticae (Acari: Tetranychidae) [19]. These results justify the need for further chromatographic and storage studies in order to better understand the toxicity mechanisms of the castor bean extract and possibly produce a commercial product that is safe for farmers and the environment.…”
Section: Resultsmentioning
confidence: 99%